A Rare Case of Neonatal Thoracotomy for a Penetrating Chest Injury Caused by a Pitbull Bite - I GNA Bayu Wiradinatha; I Made Indra Prasetya; Ni Made Sukewanti; I Ngurah Arya Wicaksana (The International Journal of Medical Science and Health Research, 2025)
Introduction: Penetrating thoracic trauma in the neonatal period is a rare and highly lethal event. Dog bites, particularly from powerful breeds, can inflict catastrophic injuries that present a formidable challenge to even the most prepared trauma centers. This report details the successful management of a neonate with life-threatening thoracic injuries following a pitbull attack. Case Report: A 2.7 kg male neonate presented in respiratory failure and shock after being mauled by a pitbull. Examination revealed an open pneumothorax, flail chest, multiple displaced rib fractures, and visible lung lacerations. After initial stabilization, he underwent an emergency left thoracotomy. The procedure involved primary repair of multiple deep lung lacerations and stabilization of the flail chest segment. The postoperative course was complex, requiring nine days of mechanical ventilation, management of atelectasis, multiple blood product transfusions, and broad-spectrum antibiotic therapy. The patient made a full recovery and was discharged after 20 days. Discussion: The successful outcome was contingent upon a rapid, coordinated, multidisciplinary response. Key interventions included immediate life-saving procedures in the emergency department, aggressive surgical control of hemorrhage and air leak, and meticulous postoperative critical care. Management focused on lung-protective ventilation, infection prevention, and nutritional support, which were crucial for navigating the complicated recovery period. Conclusion: Catastrophic thoracic trauma in a neonate, while having a grim prognosis, is survivable. This case demonstrates that immediate, aggressive surgical intervention combined with prolonged, high-acuity intensive care can lead to a positive outcome, underscoring the importance of an integrated trauma system.